Students' Reflective Abstraction in Solving Ethnomathematics-Based Mathematics Problems - Balila, Jesika Nur Intan; Putra, Eric Dwi; Lutfiyah, lutfiyah (Journal of Education and Learning Mathematics Research (JELMaR), 2023)
Reflective abstraction is a process of reflection on previously learned concepts and applied in new situations. The purpose of this study is to describe the reflective abstraction ability of junior high school students in solving math problems in terms of mathematical ability. In this study using qualitative research type. The data sources for this study were 4 students of class VIII, namely 2 students with high ability and 2 students with low ability. The results showed that students who have high ability, recognition level to remember and identify previous activities related to the problem at hand. At the representation level, students can translate information into mathematical models correctly. At the structural abstraction level, students can solve problems correctly, and are able to overcome difficulties in solving problems. At the structural awareness level, students are able to provide arguments about the results of the answers that have been done. While students with low ability, at the recognition level are able to remember previous activities related to the problem at hand. At the representation level, students are able to translate information into mathematical models, but students are less careful and wrong so that at the structural abstraction level students are able to solve problems, but the final results obtained are not correct. At the structural awareness level, students are able to solve and explain the steps in the problem. Based on the results of the study, teachers should guide students by providing problem exercises that can increase reflective abstraction, especially considering student responses and learning outcomes collected from high and low ability students. For this reason, further research needs to be carried out with other student data sources.